Importance of music learning and musicality in rhythmic gymnastics - Loo, Fung Chiat; Loo, Fung Ying (Elsevier, 2012)
Music plays an important role for sports events such as rhythmic gymnastics, synchronized swimming, skating and so forth. From a musical perspective, it is found that the lack of congruence between music and movement is observed through videos such as the Olympics and the Commonwealth Games. Interviews were conducted with coaches and the study reveals the limitations faced by coaches including the musical background of gymnasts and the editing of music for a routine. Since the correlation between movement and music is important, this paper suggests that fundamental music learning should be implemented in the training of gymnasts.